Analysis of Poland’s enotourism product model - Sidorkiewicz, Marta (Quaestiones Geographicae, 2023)
The development of winemaking has never been as dynamic as today in the whole history of Poland, with more and more vineyards being created each year. Such a state of Polish winemaking constitutes the development potential of the Polish enotourism product. The main purpose of this article is to develop the concept of the Polish tourism offer model, the target group of which are enotourists, including the identification of the elements of the enotourism offer in Poland along with a discussion of their current quantitative and/or qualitative status and recommendations for its improvement. In order to achieve the purpose of the article, a desk research method, known as a desk data analysis, was used, which involved the use of secondary data. The results of the conducted research allow concluding that Poland as a destination has a multi-element enotourism product. In the course of achieving the goal of this article, the concept of Poland’s enotourism product model was developed, within which four main elements were distinguished, i.e. natural values enabling the cultivation of grapevines, local and regional enotourism products, entities supporting and promoting enotourism in Poland, and content inspiring enotourists.